Identifying mild and severe preeclampsia in asymptomatic pregnant women by levels of cell‐free fetal DNA. Issue 9 (16th January 2013) - Jakobsen, Tanja Roien; Clausen, Frederik Banch; Rode, Line; Dziegiel, Morten Hanefeld; Tabor, Ann
<x xml:space="preserve">Abstract</x> Background The objective was to investigate whether women who develop preeclampsia can be identified in a routine analysis when determining fetal RHD status at 25 weeks' gestation in combination with PAPP‐A levels at the first‐trimester combined risk assessment for Trisomy 21. Study Design and Methods D– women participating in the routine antenatal RHD screening program in the capital region of Denmark were retrospectively studied. We used a standard dilution curve to quantify the amounts of cell‐free fetal DNA (cffDNA) and divided women into groups according to cffDNA levels. PAPP‐A was measured at 11 to 14 weeks. Information about pregnancy outcome and complications was obtained from the National Fetal Medicine Database, medical charts, and discharge letters. Results The odds ratio (OR) of developing severe preeclampsia given a cffDNA level above the 90th percentile compared to cffDNA below the 90th percentile was 8.1 (95% confidence interval [CI], 2.6‐25.5). The OR of developing mild preeclampsia given a cffDNA level below the 5th percentile compared to cffDNA levels above the 5th percentile was 3.6 (95% CI, 1.1‐11.7). PAPP‐A levels below the 5th percentile were associated with mild preeclampsia, but adding it to the analysis did not increase the detection rate (DR). Conclusion Women with cffDNA levels below the 5th percentile and above the 90th percentile quantified at 25 weeks' gestation are at increased risk of developing preeclampsia. Adding PAPP‐A levels to the analysis did not increase the DR of preeclampsia.